2018
DOI: 10.5194/bg-15-5831-2018
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of lignin oxidation products as vegetation biomarkers in speleothems and cave drip water

Abstract: Abstract. Here we present a sensitive method to analyze lignin oxidation products (LOPs) in speleothems and cave drip water to provide a new tool for paleo-vegetation reconstruction. Speleothems are valuable climate archives. However, compared to other terrestrial climate archives, such as lake sediments, speleothems contain very little organic matter. Therefore, very few studies on organic biomarkers in speleothems are available. Our new sensitive method allows us to use LOPs as vegetation biomarkers in spele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…The methods used for dating of the stalagmite samples, the analysis of trace elements and stable isotopes as well as the calculation of the drip rate for the cave drip water samples and the growth rate of the stalagmite are described in detail in Mischel et al (2017) and references therein. The method used here for the analysis of lignin oxidation products in speleothems and cave drip water is described in detail in Heidke et al (2018). In the following paragraph, only a brief description will be given.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The methods used for dating of the stalagmite samples, the analysis of trace elements and stable isotopes as well as the calculation of the drip rate for the cave drip water samples and the growth rate of the stalagmite are described in detail in Mischel et al (2017) and references therein. The method used here for the analysis of lignin oxidation products in speleothems and cave drip water is described in detail in Heidke et al (2018). In the following paragraph, only a brief description will be given.…”
Section: Methodsmentioning
confidence: 99%
“…For the drip water stable isotope and trace element data, the uncertainty is very small and therefore not shown here, but it is provided in Mischel et al (2017). For the drip water LOP data, the uncertainty was calculated as described in Heidke et al (2018), and for the stalagmite LOP data, the calculation of the uncertainty is described in section 3.2.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that trace concentrations of lignin oxidation products can be quantified in dripwater and speleothems (Heidke et al, 2018). In addition, in a Holocene stalagmite from the Herbstlabyrinth, Germany, the LOP concentrations and C/V and S/V ratios were found to co-vary with environmental changes and correlate with other proxies, such as P, U and Ba concentrations as well as δ 13 C values (Heidke et al, 2019).…”
Section: Introductionmentioning
confidence: 92%